Intelligent Systems Design and Applications 16th International Conference on Intelligent Systems Design and Applications (ISDA 2016) held in Porto, Portugal, December 16-18, 2016 - Madureira, Ana Maria; Abraham, Ajith; Gamboa, Dorabela; Novais, Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book comprises selected papers from the 16th International Conference on Intelligent Systems Design and Applications (ISDA'16), which was held in Porto, Portugal from December 1 to16, 2016. ISDA 2016 was jointly organized by the Portugual-based Instituto Superior de Engenharia do Porto and the US-based Machine Intelligence Research Labs (MIR Labs) to serve as a forum for the dissemination of state-of-the-art research and development of intelligent systems, intelligent technologies, and applications. The papers included address a wide variety of themes ranging from theories to applications of intelligent systems and computational intelligence area and provide a valuable resource for students and researchers in academia and industry alike. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence